THE RELATIONSHIP OF EPILEPTIFORM WAVES IN ELECTROENCEPHALOGRAM WITH EPILEPSY TYPE OF SCHOOL-AGE EPILEPSY PATIENTS - Jerome Constantine Lekatompessy; Bertha Jean Que; Laura Bianca Sylvia Huwae (MNJ (Malang Neurology Journal), 2023)
Background: Epilepsy in children causes memory problems in the learning process, so an early diagnosis of epilepsy is needed. The modality for determining the diagnosis of epilepsy is an electroencephalogram (EEG) examination. EEG recording results in epilepsy patients are epileptiform waves that can vary according to the type of epilepsy suffered. Objective: This study aims to determine the relationship of epileptiform waves on an electroencephalogram (EEG) with the type of epilepsy in school-age epilepsy patients. Methods: This study is an analytical study that uses secondary data in the form of medical records with cross sectional design. The research subjects were 106 patients taken with total sampling technique. Data collection is done by recording medical record data on the data collection form made by researchers. Correlation analysis between variables in this study used the Fisher test. Results: The results of this study indicate there is a relationship between epileptiform waves on the electroencephalogram (EEG) with the type of epilepsy in school-age epilepsy patients, with p = 0.018 in 0.050 significance value. Conclusion: It can be concluded that there is a correlation between epileptiform waves on an electroencephalogram (EEG) with the type of epilepsy in school-age epilepsy patients.